The role of innovation and technologies in supply chain management addressing food insufficiency in Africa - (:unkn) unknown (My University, 2025)
This Special Issue seeks to know how technological innovations can improve the local supply chain management for food self-sufficiency in Africa.It also aims to identify supply chain best practices in the food sector in a context that is characterized by high social pressure and economic disruption. It explores the dynamics of technologies and how such technologies can match the needs of supply chains and enable these economies to meet the challenge of food self-sufficiency. Furthermore, understanding how the different nodes are woven within the African supply chains would not only help in identifying improvement points but also strengthen local collaborations to face the challenges of globalization.Food Supply Chain (FSC) in Africa is characterized by the presence of many vulnerable participants such as smallholder farmers and purchasing clerks (Bai et al., 2022). Therefore, collaborative practices and transparency developed in response to economic pressures are driving the evolution of the chain and encouraging greater vertical and horizontal coordination (Matopoulos et al., 2007). The use of logistics planning models common in Western or developed countries may be ineffective in Africa due to its unique contextual characteristics. The originality of this SI lies in its focus on the examination of an FSC management model that is specific to Africa. The SI addresses the following questions: What are the difficulties around FCS in Africa? Is the issue of food insufficiency dependent on the lack of agricultural production? Could it be due to difficulties in transporting crops? Is it the inadequacy of food transformation and/or conservation units? What role can supply chain management play in addressing food insufficiency issue? What role does technology play? What are the opportunities and barriers in implementing technologies in Africa’s FCS?
Keywords: African Research